Zinc Element Traces to Inhibit Scale Formation on Cooling Tower and Air Cooler Systems - Abdul Rahman Ahmed Reshan, Shaymaa (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
Calcium carbonate is predominantly present in aqueous systems, which iscommonly used in industrial processes. It has inverse solubility characteristicsresulting in the deposition of scale on heat transfer surface. This paper focuses ondeveloping methods for inhibition of calcium carbonate scale formation in coolingtower and air cooler system where scaling can cause serious problems, ZnCl 2 and ZnI2 has been investigated as scale inhibitor on AISI 316 and 304. ZnCl 2 were moreeffective than ZnI 2 in both systems, and AISI 316 show more receptivity to thechlorides salt compared to AISI 304. The inhibitors were more effective in coolingtower than air cooler system. AISI 316 show more constant inhibition efficiency incooling tower with maximum of 95% with ZnCl 2 and 83% with ZnI 2 .